ANALISIS KESALAHAN SISWA BERDASARKAN OBJEK KAJIAN MATEMATIKA DALAM MENYELESAIKAN SOAL OPERASI HITUNG BENTUK ALJABAR - Nafai, Jessica; Sajalang, Santje M.; Pesik, Anekke (JURNAL LEMMA, 2025)
This study aims to identify errors made by students when solving mathematics problems, particularly in algebraic operations, and to analyze the factors contributing to these errors. Employing a qualitative descriptive method, the research involved 28 students. Data were collected through written tests and interviews. Interview results were used to determine the factors causing student errors in solving algebraic operation problems; written test results determined the percentage of each error type. The tests revealed that 57.14% of student errors were factual, 32.14% were conceptual, 25% were principle errors, and 64.28% were procedural.